Saved by the rancher - Ryan, Jennifer, 1973- (Ryan, Jennifer, 1973- Hunted series, 2013)
"From the moment rancher Jack Turner rescues Jenna Caldwell Merrick, he is determined to help her. Soon, he is doing more than tend her wounds; he is mending her heart. Jenna is a woman on the run--hunted down by her ex-husband, David Merrick, from the day she left him, taking part of his company with her, to the second she finds herself in the safety of Jack's ranch. More than just a haven, Jack's offering the love, family, and home she thought were out of reach. Jack's support will give Jenna the strength she needs to reclaim her life. The hunted will become the hunter, while David gets what he deserves, when they have an explosive confrontation in the boardroom of Merrick International. But not before Jack and Jenna enter into a fight ... for their lives."--Page 4 of cover.